GAYA KEPEMIMPINAN KEPALA SEKOLAH TAMAN KANAK-KANAK SE-KECAMATAN MARPOYAN DAMAI PEKANBARU - Buana, Tri Utami Santra; Zulkifli, Zulkifli; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : The background of this research was the Principal at the kindergarten level in Pekanbaru has a wide variety of leadership styles. There are many styles that are applied Principal kindergarten in performing their duties. There Headmaster entire decision must be based on him, so did not want to listen to input from teachers or subordinates. Whatever a school principal without first negotiating with the teacher. The purpose of this study was to determine the principal's leadership style and to identify trends in school leadership styles. This type of research used in this research is descriptive quantitative research. The number of objects of research as many as 32 people Headmaster. Questionnaire data collection techniques. Based on the results of existing studies it is known that, in the authoritarian leadership style, high category with 10 respondents or by 31.25%. Medium category with 15 respondents or 46.87% of. Low category with 7 respondents or by 21.87%. In a democratic leadership style, high category with 8 respondents or 25%. Medium category with 13 respondents or 40.62% of. Low category with 11 respondents or 34.37% of. In the laissez faire leadership style, high category with 8 respondents or 25%. Medium category with 12 respondents or 37.5%. Low category with 12 respondents or 37.5%.Keywords: Leadership Style, Head of School